2001
DOI: 10.1111/j.1553-2712.2001.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directives in Skilled Nursing Facility Residents Transferred to Emergency Departments

Abstract: Abstract. Objective: Ten years have passed since Congress enacted the Patient Self-Determination Act to promote the use of advance directives (ADs). This study was performed to determine the frequency, type, demographic distribution, and utility of ADs that accompany residents of skilled nursing facilities (SNFs) transferred to emergency departments (EDs). Methods: This was an observational, cross-sectional cohort of SNF residents, transferred to two urban, academic EDs. Chart review and physician interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 5 publications
4
49
1
Order By: Relevance
“…Some authors have shown a relationship with race, which was not found in this study, possibly due to the inclusion of confounders in past analyses. 8,9,11,12 In the multivariate analysis, patients of increasing age were significantly more likely to present with a DNR order. Previous studies have consistently demonstrated similar associations with age.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Some authors have shown a relationship with race, which was not found in this study, possibly due to the inclusion of confounders in past analyses. 8,9,11,12 In the multivariate analysis, patients of increasing age were significantly more likely to present with a DNR order. Previous studies have consistently demonstrated similar associations with age.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have consistently demonstrated similar associations with age. 8,9,14,22 Age was broken out further in Table 2, and demonstrated significant associations with the presence of DNR orders, living wills, and healthcare POAs. While the oldest of the geriatric population has a high prevalence of POA (59.5%), living will (40.5%) and DNR orders (40.5%), the younger geriatric population has a significantly lower prevalence of these documents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of life should never be used as a criterion to withhold CPR, because conditions such as irreversible brain damage or brain death cannot be reliably assessed or predicted. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Out-of-hospital DNAR protocols must be clear to all involved (eg, physicians, patients, family members, loved ones, and out-of-hospital healthcare providers). Advance directives can take many forms (eg, written bedside orders from physicians, wallet identification cards, identification bracelets, and other mechanisms approved by the local emergency medical services [EMS] authority).…”
Section: Issues Related To Out-of-hospital Resuscitationmentioning
confidence: 99%